PELATIHAN MICROSOFT OFFICE UNTUK MENINGKATKAN KINERJA APARATUR DESA SUNTENJAYA - Mishelei Loen (Lembanga Pengabdian Masyarakat, 2023)
Suntenjaya Village is a village with land conditions in the form of slopes/ridges. Suntenjaya Village which is included in the administrative area of ​​Lembang District, West Bandung Regency. Suntenjaya Village which is included in the administrative area of ​​Lembang District, West Bandung Regency. The residents of Suntenjaya village are generally engaged in agriculture and labor. Fewer people who work as farmers, farm labore rs, day laborers, and private workers. The village government is the village head or what is called by another name related to the village apparatus, Suntenjaya village officials are still not familiar with information technology, among others in the computer world. Seeing the job opportunities above, the village apparatus needs to be given knowledge in supporting their work and activities, to facilitate their work in managing village administration, and to be able to convey their knowledge to the community in their environment. Village officials will be given computer introduction materials which are then equipped with Microsoft Office applications. The goal is to provide training, improve and develop knowledge about village officials and involve the role of teachers in education as a form of community service carrying out the duties of the Tri-Dharma of Higher Education. The method used is the method of practice and question and answer. So that after training, village officials can operate computers and use Microsoft Office well. Computer training on Sukadaya village apparatus, can be used to manage computers properly and master Microsoft Office, to improve performance and be able to compete in the era of globalization.